Ответы и объяснения

  • Участник Знаний
2013-11-15T06:33:22+00:00
А)
х/2+у/3=3     умножим на 2 : х+у*2/3=6  (1)
х/3+у/2=1/3  умножим на 3 : х+у*3/2=1  (2)
вычитаем (2) из (1)
 х+у*2/3 - (x+y*3/2) = 6 -1
 у*2/3 - y*3/2 = 5
y (2/3 - 3/2) = 5
y = - 6
из (1) х+(-6)*2/3=6 ; x -2*2 = 6 ; x = 10
ответ (10; -6)

б)
х/3+у/2=5   умножаем на 15 : 5x +y * 15/2 = 75 (1)
5х-11у=1    (2)
вычитаем (2) из (1)
5x +y * 15/2 - (5x -11y)= 75 - 1
y * 15/2 +11y= 74
y (15/2 +11) = 74
y =4
из (2) считаем х
5х-11*4=1
5x = 45
x = 9
ответ (9; 4)